Pengaruh Pengalaman Merek Terhadap Kecintaan pada Merek Krispy Kreme dengan Keaslian Merek Sebagai Variabel Mediasi - Christopher Steven Widodo; Richard Andrew (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The purpose of this research is to determine the influence of brand experience and brand authenticity on brand love, the influence of brand experience on brand authenticity, and the influence of brand experience on brand love in Krispy Kreme consumers with brand authenticity as a mediating variable. The population of this research is all Krispy Kreme consumers in Jakarta and the sample selection used purposive sampling and the sample size was 100 respondents domiciled in Jakarta. This research uses primary data obtained by distributing questionnaires online using Google forms. The data analysis technique uses PLS-SEM with the help of the SmartPLS program. The research results directly show that brand experience and brand authenticity influence brand love. Brand experience influences brand authenticity. Brand experience influences brand love among Krispy Kreme consumers with brand authenticity as a mediating variable.